Evaluation of Bahasa Malaysia courseware for hearingimpaired student / Siti Salbiah Hamzah, Normalina Ibrahim and Ummu Fatihah Bahrin - Hamzah, Siti Salbiah; Ibrahim, Normalina; Bahrin, Ummu Fatihah (Universiti Teknologi MARA, Perak, 2018)
Courseware learning is learning educational curriculum outside of a traditional classroom. It consists of multimedia element such as text, sound, image, video and animation to help students understanding on particular subject or topic. Kids with disability have difficulties to learn something new especially kids with hearing impaired. Therefore, Bahasa Malaysia Courseware for Hearing Impaired Student (eBM) is designed to help student to improve their understanding about Bahasa Malaysia subject. A preliminary study has been conducted and a suitable method was chosen to develop prototype of this courseware. An expert evaluation were conducted to identify perception of users and user acceptance of this courseware in order to verify the requirement for assistive courseware that address hearing impaired needs in the context of multimedia elements, content and structure of the courseware and also sign language.